The Implementation of E-Procurement in Indonesia: Benefits, Risks, and Problems - Nurus Sa'adah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
E-procurement was a new model of muamalah applied in the procurement in several countries in the world. Indonesia was implemented from 2010, but the implementation was not maximal. Proven there were still doubts to use this modern muamalah model. So, this research aimed to find information on how e-procurement was implemented in Indonesia. Data were obtained from a questionnaire containing a list of structured and open questions provided to government agency procurement officers, provider staff, and secondary data from e-procurement research in several local governments in Indonesia.  The results showed that the implementation of e-procurement reduced fraud. Benefit (maslahah) e-procurement was proven to be more than the risk (mafsadat). There were still doubts about sharia in the implementation of procurement due to a lack of information. The implementation of e-procurement still needs the attention to strengthening the quality of procurement officials, regulations, supervision, and internet support so that e-procurement success.